State-resolved femtosecond phase control in dense-gas laser-atom interaction enabled by attosecond XUV interferometry - Hedewig, Lina; Kleine, Carlo; He, Yu; Wieder, Felix; Ott, Christian; Pfeifer, Thomas (Optics letters, 2025)
We perform an interferometric measurement of an extreme ultraviolet (XUV) pulse passing through a dense gas-phase target. Utilizing the interaction with strong and narrow atomic resonances, we demonstrate the femtosecond phase control of the resonant XUV pulse propagation by means of a time-delayed intense near-infrared (NIR) laser pulse. XUV spectral interferometry provides direct access to the amplitude and phase of the transmitted pulse and thus enables the full reconstruction of the ultrafast dynamics. We benchmark our measurement approach with the singly excited 1 - s - 4 - p - Rydberg state of helium to directly reconstruct the temporal structure of the transmitted XUV pulse beyond the single-atom response. An NIR-intensity-controlled variable phase step between 0 and 2 rad is measured on the XUV pulse after passage through the medium, originating from laser-induced transient Stark shifts.
Gesehen am 25.08.2025